1996
DOI: 10.1002/(sici)1099-1166(199607)11:7<613::aid-gps357>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Medical illness, religion, health control and depression of institutionalized medically ill veterans in long-term care

Abstract: Utilizing multivariable multivariate regression procedures, we examine the relationships among medical illness, religion, health control beliefs and depression in 97 mostly elderly, institutionalized medically ill veterans in long term‐care. Controlling for other domains of indicators, conditional canonical correlations showed that (1) religious motivation alone predicts religious coping, (2) religious coping alone predicts health control beliefs, and (3) both severity of illness/length of stay and health cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…They found that religious beliefs, including God concept, were significantly related to both self-reported religious behaviors and religious motivation. Other research has also supported the religious motivation-coping link (Grosse-Holforth et al 1996). The assumption here is that belief in a loving, benevolent deity will produce different behaviors than the belief in a cruel, distant, or punishing God.…”
Section: The Role Of Reasoned Action In Copingmentioning
confidence: 79%
“…They found that religious beliefs, including God concept, were significantly related to both self-reported religious behaviors and religious motivation. Other research has also supported the religious motivation-coping link (Grosse-Holforth et al 1996). The assumption here is that belief in a loving, benevolent deity will produce different behaviors than the belief in a cruel, distant, or punishing God.…”
Section: The Role Of Reasoned Action In Copingmentioning
confidence: 79%
“…Given Filipinos commonly use faith-based coping strategies, it is not surprising they also scored highly on the spirituality domain. Religious practice has been shown to augment social support and coping skills in the face of adversity, whilst providing a buffer against stressful life events [ 43 , 44 ] and this ‘buffering’ or inter-relationship between various aspects of PMH may explain why spirituality along with other domains such as GC and ES were also higher amongst certain ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that being religious may have a positive effect on the outcome of depression, increasing the speed of recovery ( Koenig, 1997 ; Koenig et al, 2001 ). Religious communities and faith-based organizations provide social support and religious belief systems offer meaning and hope about the future as well as providing the individual with a means of coping in the midst of suffering ( Grosse-Holforth et al, 1996 ; Koenig et al, 2001 ; Krause, 1995 ; Tix & Frazier, 1998 ). Koenig and colleagues (1992) showed, in a study examining the relationship between depression and the use of religion as a coping behaviour in hospitalized medically ill men, that the only characteristic that predicted lower rates of depression six months later was the extent to which patients relied on their religious faith to cope.…”
Section: Introductionmentioning
confidence: 99%